Safety Profile of Subjects Treated to Very Low Low-Density Lipoprotein Cholesterol Levels (<30 mg/dl) With Rosuvastatin 20 mg Daily (from JUPITER) - Everett, Brendan M.; Mora, Samia; Glynn, Robert J.; MacFadyen, Jean; Ridker, Paul M. (The American journal of cardiology, 2014)
Recent US guidelines expand the indications for high-intensity statin therapy, yet data on the safety of attaining very low-density lipoprotein cholesterol (LDL-C) levels are scarce. Among 16,304 participants in the Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin (JUPITER) with on-treatment LDL-C levels, we identified 767 who did and 7,387 who did not achieve LDL-C <30 mg/dl on rosuvastatin 20 mg daily and 718 participants who did and 7,436 who did not achieve LDL-C reductions of ≥70% on rosuvastatin, and 8,150 allocated to placebo. In participants with an LDL-C <30 mg/dl, we observed an increase in the risk of physician-reported type 2 diabetes with an adjusted hazard ratio (95% confidence interval) of 1.56 (1.09 to 2.23, p = 0.01) and physician-reported hematuria (hazard ratio 2.10 [1.39 to 3.19], p <0.001) compared with rosuvastatin-treated participants with LDL-C ≥30 mg/dl. There was also an increased risk of certain musculoskeletal, hepatobiliary, and psychiatric disorders. No difference in renal failure, cancer, memory impairment, or hemorrhagic stroke was observed, although there were few events in these categories. In rosuvastatin-treated participants, achieving LDL-C reduction ≥70% versus <70% did not appear to be associated with increased risk of hepatobiliary, renal, or urinary disorders. In conclusion, in this post hoc analysis in the JUPITER, achieving LDL-C levels <30 mg/dl with high-intensity statin therapy appeared to be generally well tolerated but associated with certain adverse events, including more physician-reported diabetes, hematuria, hepatobiliary disorders, and insomnia. These data may guide the monitoring of patients on intensive statin therapy and adverse events in trials of therapies that lead to very low LDL-C levels. •Approximately 10% of participants in the Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin achieved low-density lipoprotein cholesterol (LDL-C) <30 mg/dl on rosuvastatin.•The rate of adverse events in those with LDL-C <30 mg/dl on a statin was low.•However, there was a modest increase in diabetes and hematuria in patients with LDL-C <30 mg/dl.•No increased risk of diabetes or hematuria was seen for patients with large (≥70) percent reductions in LDL-C.